Empowering Marginalized Communities through Social Entrepreneurship: A Pathway to Inclusive Economic Development - Nurfaisah; Hardianti Pertiwi (Cendekiawan Indonesia Timur, 2025)
Social entrepreneurship has emerged as a transformative approach to addressing economic and social inequalities by empowering marginalized communities through innovative and sustainable business models. Unlike traditional business enterprises that prioritize profit maximization, social entrepreneurship integrates economic objectives with social impact, fostering inclusive development and long-term community resilience. This study explores the role of social entrepreneurship in promoting economic inclusion, particularly for marginalized groups such as low-income communities, women entrepreneurs, people with disabilities, and indigenous populations. Utilizing a qualitative research approach, this study examines case studies of social enterprises that have successfully uplifted marginalized communities through capacity-building, financial inclusion, and employment generation. Findings reveal that social entrepreneurs implement diverse strategies, including skills training programs, microfinance initiatives, and market access facilitation, to enable self-sufficiency and sustainable livelihoods. However, challenges such as limited funding, regulatory barriers, and scalability constraints hinder the growth of social enterprises. The study highlights the critical role of government policies, private sector collaborations, and social innovation ecosystems in overcoming these challenges and ensuring the sustainability of impact-driven enterprises. This research contributes to the broader discourse on inclusive economic development by emphasizing the need for a multi-stakeholder approach to fostering social entrepreneurship. It argues that empowering marginalized communities through entrepreneurial initiatives requires a combination of policy support, social investment, and digital transformation. The study provides policy recommendations for strengthening social enterprise ecosystems and enhancing their capacity to drive long-term socio-economic change.